The Interrelationship of Planning, Participation and ICT: the Case of Developing a Curriculum in Agia Varvara, Athens, Greece - Alex Deffner; Vassilis Bourdakis (European Regional Science Association (ERSA), 2006)
One of the main problems in recent urban planning is how to make more practical very broad and commonly used theoretical, and interrelated, principles such as sustainability and governance. The main aim of the paper is to demonstrate how one of the main issues of urban governance, i.e. public participation in planning, can be helped through the use of new technologies. The data are provided by the PICT (Planning Inclusion of Clients through e-training) project which was a three-year (2002-5) pilot project co-funded by the Leonardo da Vinci Programme of the European Commission. The main aim of the project was to encourage and facilitate effective public participation in planning by providing the necessary skills to planners and the public to communicate with each other and by developing the appropriate tools that would make such communication meaningful. The project addresses all participants in the planning process, the key objectives being to introduce key IT skills, fight technophobia and disbelief, improve communication skills, acquire an understanding of the built environment and spatial representations, and finally introduce game like activities to implement VR support tools. The PICT partners came from the UK, Greece, Belgium and Hungary. The Project Contractor was Knowsley Metropolitan Borough Council (UK) and the Project Coordinator was PRISMA Centre for Development Studies (Greece). The paper focuses on the curriculum developed for the Municipality of Agia Varvara which lies to the west of the City of Athens. It has a population of approximately 30,500 people with a multicultural identity and high unemployment rates. The developed curriculum consists of three parts: a 'core' part that is shared by both planners and the public, and two distinct parts: one addressing the public and the other the planners. Each part consists of several modules, to cater for different learning levels, abilities and interests. The structure is flexible and the whole idea was to have a curriculum with a scientific, and not a 'journalistic', basis that could, at the same time, be simple, but not simplistic.
Keywords: 330